The Influence of Relationship Marketing and Word-Of-Mouth On Service Selection Decisions with Trust as A Mediating Variable - Fadhila Azzahra; Tibrani Tibrani; Rizki Eka Putra (Program Studi Akuntansi Universitas Simalungun, 2026)
Patient behavior in selecting clinical laboratory services is heavily influenced by the quality of interactions and recommendations they receive. However, a research gap exists regarding the psychological mechanisms driving these choices in